Pengaruh Kualitas Jasa Pendidikan Terhadap Kepuasan Mahasiswa di Universitas Pendidikan Indonesia - Anggi Rustami, Nenden; ,, Nuraedi; Chusnul Kurniatun, Taufani (Jurnal ADPEND, 2016)
This study entitled "Effect of Service Quality Education Student Satisfaction at the university education of Indonesia ". The problem that the writer suggested in this study is the student satisfaction about the quality of education services in university education of Indonesia. In general, this study aims to determine the effect of the quality of educational services to the student satisfaction at the university education of Indonesia. The method used in this research is descriptive with quantitative approach. Data collection techniques using a questionnaire that is through online by using google form and a questionnaire to the respondent directly spread through print out the questionnaire, the number of questionnaires that are spread as much as 99. The result of the calculation Weight Mean Score (WMS), showed that the quality of educational services included in the high category with a score of 3.69 and student satisfaction with a score of 3.68, including the high category. Analysis of the correlation between the quality of educational services to the student satisfaction has a strong relationship with a correlation coefficient of 0.724. The regression equation of these two variables, namely Y = 10 175 + 0.820X, this means every one-unit change in the quality of education services will provide updates to the satisfaction of the students of 0,820. The results of significance test using t-test, namely t hitung (10,350)> t_tabel (1.984) means that there is a significant relationship between the variables X and Y, then the coefficient of determination test results showed that the degree of connectedness between the quality of educational services to the student satisfaction affects 52.5 % while the remaining 47.5% influenced by other factors not examined. It is concluded that there is a positive and significant relationship between the quality of education services to the satisfaction of students in university education Indonesia.